Multidimensional and transient modeling of an alkaline water electrolysis cell. (14th April 2021) - Lee, Jaeseung; Alam, Afroz; Ju, Hyunchul
Abstract: A three-dimensional (3-D) transient numerical model of an alkaline water electrolysis (AWE) cell with potassium hydroxide solution is developed by rigorously accounting for the hydrogen and oxygen evolution reactions and resulting species and charge transport through various AWE components. First, the AWE model is experimentally validated against a polarization curve corresponding to a wide range of currents as high as 2.0 A·cm −2 . In general, the simulation results compare well with the measured data and further reveal the operating characteristics of AWE cells, showing key distributions of solid/electrolyte potentials and multidimensional contours of reactant and product concentrations at various current densities. In particular, the contribution of hydroxide ion (OH − ) diffusion to the ohmic losses through porous electrodes and a porous separator are quantitatively examined at low and high electrolyte flow rates. The present full 3-D AWE model provides a basic understanding of the electrochemical and transport phenomena and can be further applied to practical large-scale AWE cell and stack geometries for grid-scale hydrogen production. Highlights: A developed model elucidates the electrochemical reactions and transport phenomena. The model was successfully validated against the experimental I–V curve. The OH − diffusion impact was negligible because of the high flow rate of electrolyte.